COMPARATIVE IN-VITRO BIOEQUIVALENCE STUDY OF BRANDED AND GENERIC AMOXICILLIN CAPSULE IN FOUR - Usman M. A; Bello I.; Awwalu S; Victor, E, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2017)
Comparative in-vitro bioequivalence study using dissolution profile data of immediate release oral solid dosage form of Biopharmaceutics class 1 and 3 has been advocated by World Health Organization (WHO), Food drugs Administration (FDA) and other international regulatory agencies. In-vitro dissolution offered many benefits compared to conventional in-vivo bioequivalence studies because, it reduces the cost and time of product release as well as avoiding unnecessary use of human volunteers thereby improving access to drugs from multisource for all persons as encouraged by WHO, to guarantee right to health for all.To evaluate and compare the in-vitro dissolution profiles of branded and generic brand of amoxicillin capsules available in Dutse, Jigawa, Nigeria.Dissolution profiles of branded and generic amoxicillin capsules containing amoxicillin 500 mg which are available in Dutse market were determined using the developed UV spectrophotometric method. The obtained dissolution profile data were assessed and comparedusing two different statistical methods: the fit factors (F1&F2) and the dissolution efficiency (D.E.) model. The tested generic brand of amoxicillin capsule can be interchangeable with the innovator brand. The computed F1 factor for the Generic brand are3.35, 6.12, 8.83 and 7.94 for simulated physiological pH (1.2, 4.5, 6.8 and 7.4) respectively which are within the acceptable limit of (0-15). While the F2 factor values are 69.00,57.15, 42.67and 46.76 for simulated physiological pH (1.2, 4.5, 6.8 and 7.4) where at SGF (pH 1.2) and Buffer (pH 4.5) were within the recommended range of ≥50 while values at SIF and Blood (pH 6.8 and 7.4) falls short of the accepted limit of ≥50. Similarly, the mean dissolution efficiencies (D.E.) were 4.00, 6.885.19 and 2.05 which are within the acceptable limit of ±10 for pH (1.2, 4.5, 5.19 and 7.4 respectively).Therefore, tested generic brand of amoxicillin capsule was found to be similar with the innovator brand, thus can be interchangeable with each other in clinical use.